A study in scarlet - Doyle, Arthur Conan, Sir, 1859-1930. (New York : Penguin, 1981)
Sherlock Holmes and his assistant, Dr. Watson, investigate the murder of an American and his private secretary.
Young Adult
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Holmes, Sherlock (Fictional character) -- Fiction; Mystery fiction; Private investigators -- Fiction; England -- Fiction; England -- Fiction; Detective and mystery stories